Indeks Kepuasan Masyarakat Terhadap Layanan Infrastruktur Di Kecamatan Ujung Pangkah Kabupaten Gresik - Roziana Ainul Hidayati (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background : Based on the results of research in the coastal area of ​​Gresik Regency in Ujungpangkah District and Panceng District, it is known that the category of Developing Village in Ujung Pangkah District is Pangkah Kulon Village, Banyu Urip Village, Bolo Village, Pangkah Wetan Village, Gosari Village, Cangaan Village, Karangrejo Village, Tanjang cloud Village, Glatik Village, Ketapang Lor Village and Ngemboh Village. Meanwhile, Sekapuk Village is the only independent village in Ujungpangkah District. Meanwhile, Kebonagung Village is the only Disadvantaged Village in Ujungpangkah District. The average IPD variable whose condition is lagging and not yet independent occurs in almost all villages in Ujung Pangkah District. Based on this, the researcher intends to follow up by measuring community satisfaction with the availability of infrastructure in Ujung Pangkah District. Purpose : The measurement of community satisfaction is intended to find out how far the actual level of community satisfaction with the availability of infrastructure is still minimal. Design/Methodology/Approach : Research on the Community Satisfaction Index for Infrastructure Services in Ujung Pangkah District by taking the research area is all villages in Ujung Pangkah District except Sekapuk Village using descriptive quantitative methods. Result and Discussion: The results of the study indicate that the Road Infrastructure Service Satisfaction Index obtained a value of 79.03 with service quality category B (Good). The land transportation infrastructure service satisfaction index obtained a value of 68.06 with the quality of service included in category C (less good). The Health Infrastructure Service Satisfaction Index obtained a value of 77.92 with service quality including category B (Good). The Education Infrastructure Service Satisfaction Index obtained a value of 76.39 with service quality including category C (less good). The Clean Water Infrastructure Service Satisfaction Index obtained a value of 82.22 with service quality including category B (Good). The Housing Infrastructure Service Satisfaction Index obtained a value of 74.31 with service quality including category C. (less good). Conclusion: the Road Infrastructure Service Satisfaction Index category B. The land transportation infrastructure service satisfaction index category C. The Health Infrastructure Service Satisfaction Index category B. The Education Infrastructure Service Satisfaction Index category C (less good). The Clean Water Infrastructure Service Satisfaction Index category B (Good). The Housing Infrastructure Service Satisfaction Index category C. Research Limitation: the research area is all villages in Ujung Pangkah District except Sekapuk Village Research Implication: These results imply that it is necessary for the sub-district and related agencies to repair infrastructure whose value is still category C or less good, and infrastructure that has a value of category B, can be improved again to a better service or Category A Acknowledgement: This research was carried out in collaboration with UjungPangkah District and was funded by the Institute for Research and Community Service (LPPM) Universitas Muhammadiyah Gresik.